SOSIALISASI PEMANFAATAN TANAMAN OBAT ANTI HIPERTENSI DI DESA MULYOHARJO KECAMATAN BTS ULU - Merti Triyanti; Ivoni Susanti; Sulistiyono Sulistiyono; Yeni Asmara (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2023)
Hypertension is an increase in blood pressure in the arteries. In general, hypertension is an asymptomatic condition, in which abnormally high pressure in the arteries increases the risk of stroke. This community service program is motivated by the large number of anti-hypertensive medicinal plants that are not yet known and used around the house. In addition, many people suffer from hypertension and need traditional medicines which have fewer side effects. The use of medicinal plants as antihypertensive agents is an alternative to chemical drugs which tend to have side effects. The method used in community service is socialization, the results of the implementation of community service activities are followed enthusiastically by the people of Mulyoharjo Village, Ulu BTS District. The output target to be achieved by the proposing team is to increase public knowledge in utilizing anti-hypertensive medicinal plants.